2012
DOI: 10.1177/0095327x12456509
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Civil–Military Gap

Abstract: The authors suggest that scholars mean very different things when they refer to the civil–military gap. To illustrate the point, the authors conceptualize the gap in terms of four distinct ideal types and show that scholars have referred to each variant as the civil–military gap at different times. Though the authors recognize that the four ideal types—cultural, demographic, policy preference, and institutional—are not always mutually exclusive, the authors suggest that they are divergent enough to warrant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…Second, the concept of the military in politics and its influence not only captures the idea of the military institution and its political power even when it does not seize direct power through a takeover, but also allows us to examine and recognize the political nature of the military both in democratic and authoritarian regimes. Third, differences existing in the policy objectives pursued by civilian and military policymakers could impact the policy decision process and outcome (Rahbek-Clemmensen et al, 2012).…”
Section: Civil-military Relation: Concepts and Consequencesmentioning
confidence: 99%
“…Second, the concept of the military in politics and its influence not only captures the idea of the military institution and its political power even when it does not seize direct power through a takeover, but also allows us to examine and recognize the political nature of the military both in democratic and authoritarian regimes. Third, differences existing in the policy objectives pursued by civilian and military policymakers could impact the policy decision process and outcome (Rahbek-Clemmensen et al, 2012).…”
Section: Civil-military Relation: Concepts and Consequencesmentioning
confidence: 99%
“…Although fierce disagreements on its implications persist, much of this research draws on the idea of a gap between civilian society and the military. Recently, it has been suggested that the notion of a unitary gap is too simple and four types of gaps-cultural, demographic, policy preference, and institutional-have been offered (Rahbek-Clemmensen et al, 2012). rather than complying with laws outs of fear.…”
Section: Civil-military Relationsmentioning
confidence: 99%
“…Thus, demobilization of the state has weakened the relationship between it and war. Scholarship on the civil-military gap provides additional evidence of that (Rahbek-Clemmensen et al 2012). The civil-military gap alludes to the fact that the military and society are drifting apart with respect to culture, attitudes, socioeconomic status (SES), ethnicity, and gender.…”
Section: Converging Forces and The Culminating Cultural Rmamentioning
confidence: 99%